THE INFLUENCE OF THE USE OF INFORMATION AND ORGANIZATIONAL COMMUNICATION TECHNOLOGY ON THE PERFORMANCE OF VILLAGE APPARATUS IN PASIR DISTRICT EAST LAMPUNG SAKTI - Aliyah, Hikmatul; Buchori, Buchori; Anhari, Ahmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
For the development of public services, government organizations need to be able to create and enhance services. Resources are necessary for all organizations, including governmental and commercial ones, to accomplish their objectives. One organizational resource that is essential to reaching shared objectives is human resources. The public expects the government to provide quality services. Performance evaluations are given to employees. Village authorities in the Pasir Sakti District of East Lampung are among the staff members whose work is evaluated and in need of improvement in order to promote organizational performance. The degree of service provided by village government personnel is measured by their performance.